Penguatan Pedagogi Guru melalui Pelatihan Pengembangan Bahan Ajar Video: indonesia - Ardiansyah, Arief; Akbar, Mukhammad Naafiu; Budiya, Bahroin (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Teachers' low level of knowledge and skills in designing and developing digital learning media in the form of video teaching materials hinders the efficiency of learning in the classroom. This service aims to provide training so that teachers at MI Islamiyah and SMPI Al-Hidayah, Malang City, have the knowledge and skills to independently develop digital teaching materials in the form of learning videos to increase the effectiveness, efficiency, and attractiveness of their learning. The method used in this service activity is the on-the-job training (OJT) method. This method allows teachers to receive training directly in the classroom, not in a simulated environment. The effectiveness of the training was obtained through survey techniques using participants' assessment instruments regarding the training process that had been carried out. The conclusion obtained after conducting the survey was that the average score received from the weight of the five items was 85%. The percentage of 85% shows that most teachers felt that the training activities were beneficial, so they participated enthusiastically in this training.